Shield construction safety risks and their interrelations analysis of subway tunnel undercrossing a river based on Grey-DEMATEL-ISM - Xue, Yu; Luo, Xun; Li, Hujun; Liu, Jie (Frontiers in Public Health, 2025)
A large number of subway projects were designed and constructed by China’s city government and more subway tunnels can hardly avoid undercrossing a river. Shield construction of subway tunnel undercrossing a river (STUR) is often in a complicated geological environment, which cause the construction process more prone to safety accidents. Hence, it is necessary to investigate the shield construction safety risks (SCSRs) of STUR in advance. The paper identified the related SCSRs of STUR using literature review and experts’ discussion, put forward a hybrid approach to examine the safety risks and their interrelations by integrating grey number, DEMATEL and ISM, and then selected a case to validate the feasibility of the proposed safety risk list and hybrid approach. Research results show that (a) a SCSRs list of STUR was identified, including 4 safety risk categories and 32 safety risks; (b) the proposed safety risk list and hybrid approach can be utilized to identify safety risks and analyze the significance and interrelation structure of the identified SCSRs of STUR; (c) most natural environment safety risks (levee, quick sand layer and high water pressure), management environment safety risks (safety institution and safety organization & duty) and manager safety risks (safety inspection, safety management competency) are salient safety risks; (d) the established safety accident causation structure, from the bottom up, includes environment safety risk level, personnel safety risk level, technology safety risk level, machine safety risk level, and accident level. The research can enrich the theoretic knowledge in shield construction safety risk analysis of STUR, and offer references for safety managers to carry out onsite scientific and effective safety management of STUR shield construction.